Coronary artery fi stulas in children: Experience from a Southern African tertiary care centre complex - Cilliers, A.M.; Hendson, W.; Motara, F.; Adams, P.E.; Dumani, G.; Ntsinjana, H. (SA Heart Journal, 2017)
Coronary artery fi stulas (CAF) are unusual coronary artery connections with low pressure cardiac chambers or vessels. The majority are congenital, but can also be acquired. Complications include heart failure, myocardial infarction and arrhythmias. Symptomatic and large CAF require treatment and options include surgical ligation or percutaneous device embolisation of the fi stula which has emerged as a less invasive and equally effi cacious management modality. Careful interrogation of the CAF is required prior to occlusion in order not to compromise normal coronary artery vasculature that may arise from the fi stula which can lead to myocardial ischaemia and infarction. Several reported cases highlight thrombus formation within large CAF after surgical ligation with propagation of the thrombus into coronary vessels arising proximally, resulting in myocardial compromise. We present a series of 6 children with CAF, 2 were treated by percutaneous embolisation (one developed a myocardial infarction post procedure) and 3 were treated surgically.